The development of ventricular fibrillation due to etomidate for anesthetic induction: a very rare side effect, case report - Karcioglu,Murat (2014)
Background and objectives:Ventricular fibrillation occurring in a patient can result in unexpected complications. Here, our aim is to present a case of ventricular fibrillation occurring immediately after anesthesia induction with etomidate administration.Case report:A fifty-six-year-old female patient with a pre-diagnosis of gallstones was admitted to the operating room for laparoscopic cholecystectomy. The induction was performed by etomidate with a bolus dose of 0.3 mg/kg. Severe and fast adduction appeared in the patient's arms immediately after induction. A tachycardia with wide QRS and ventricular rate 188 beat/min was detected on the monitor. The rhythm turned to VF during the preparation of cardioversion. Immediately we performed defibrillation to the patient. Sinus rhythm was obtained. It was decided to postpone the operation due to the patient's unstable condition.Conclusion:In addition to other known side effects of etomidate, very rarely, ventricular tachycardia and fibrillation can be also seen. To the best of our knowledge, this is the first case regarding etomidate causing VF in the literature.